ASCOT redevelopment and expansion - Dela Cruz, John Benedict C. (Manila : National University, 2016)
Converting Aurora State College of Technology from commuter campus to a residential campus by adding up student dwellings in the form of dormitories.
Chapter 1. The Problem and it's settings -- Chapter 2. Research Methodology -- Chapter 3. Terms and Reference -- Chapter 4. Data Gathering, Collection and Analysis of Data -- Chapter 5. Design Framework -- Chapter 6. Translations -- Bibliography -- Appendices.
Includes bibliographical references.